Interactive effects of in situ rainwater harvesting techniques and fertilizer sources on mitigation of soil moisture stress for sorghum (Sorghum bicolor (L.) Moench) in dryland areas of Tanzania. Issue 6 (2nd November 2018) - Mahinda, Athuman; Funakawa, Shinya; Shinjo, Hitoshi; Kilasara, Method
ABSTRACT: Nutrient deficiency, high rate of evapotranspiration, and insufficient and erratic rainfall are the critical challenges for crop production in the dryland areas (DLAs) of Sub-Saharan Africa, including Tanzania, where 61% of arable land is prone to drought. In addressing these challenges, field trials were conducted in central Tanzania to evaluate the interactive effects of ripping and tie-ridges with organic (FYM) and inorganic fertilizers (N) on the mitigation of the critical period of soil moisture stress (CPSMS) for sorghum yield performance. Both in situ rainwater harvesting techniques (IRWHT) and flat-cultivated land were integrated with 8 Mg FYM ha –1, 70 Kg N ha –1, and a combination of 35 Kg N ha –1 and 4 Mg FYM ha –1 (N+ FYM). Among the IRWHT, tie-ridges stored a significant water volume of 577 and 457 m 3  ha –1, which mitigated the CPSMS by the maximum of 95% and 37% for the above-average rainfall and below-average rainfall season, respectively. However, it only registered the highest grain yield (2.02 Mg ha –1 ) and biomass (3.46 Mg ha –1 ) in a below-average rainfall season. The highest overall grain yield (5.73 Mg ha – ) and biomass (12.09 Mg ha –1 ) were harvested in ripping with combined fertilizer treatments in an above-average rainfall season, while the lowest grain yield (0.5 Mg ha –1 ) and biomass (1.2 Mg ha –1 ) were registered in the flat-cultivation control in the below-average rainfall season. In the latter season, IRWHT increased the mitigation potential in the order; flat cultivation < ripping < tie-ridges; and sorghum yield, highly correlated with drought mitigation index. The results showed that sorghum grain yield and final biomass performance depend on the influence of IRWHT applied, rainfall amount, soil moisture level, integrated fertilizer, and length of the CPSMS. In the above-average rainfall seasons, fertilizers mask the influence of the IRWHT. The opposite is true in the below-average rainfall season. Although ripping– N+ FYM resulted in the highest overall yield, the study recommends practicing tie-ridges integrated with N+ FYM due to regular occurrences of low and unreliable rainfall in the dryland areas.